Treatment intensification without improved HbA1c levels in children and adolescents with Type 1 diabetes mellitus. Issue 4 (6th October 2015) - Sildorf, S. M.; Hertel, N. T.; Thomsen, J.; Fredheim, S.; Hastrup, H.; Pipper, C.; Hertz, B.; Svensson, J.
Abstract: Aims: To examine trends in diabetes treatment in Danish children and adolescents with Type 1 diabetes mellitus, comparing treatment intensity with metabolic outcomes in the population, and to describe the challenges of population‐based registries in a clinical setting with rapidly changing treatment methods. Methods: This observational study is based on the Danish national population registry of childhood diabetes, which includes 99% of children diagnosed with Type 1 diabetes before the age of 15 years. We included 4527 people diagnosed between 2000 and 2012. Self‐monitored blood glucose measurements, insulin injections/boluses, treatment method and metabolic control quantifications were analysed and adjusted for the effects of gender and ethnicity, the combined effect of age, visit year and duration, and for the random effects of individual and hospital settings. Results: Treatment was intensified via an increasing number of self‐monitored blood glucose measurements and injections/boluses. More than six injections/boluses and an increased number of self‐monitored blood glucose measurements were significantly associated with lower metabolic control. No reduction, however, in the overall mean HbA1c concentration was observed between 2005 [66 mmol/mol (8.2%)] and 2012 [65 mmol/mol (8.1%)]. Changed registration practices in 2009 introduced artificial jumps in data. Conclusions: Intensifying treatment alone does not lead to improved metabolic control in the overall population despite the appearance of lower HbA1c in individuals with a greater number of self‐monitored blood glucose measurements and injections/boluses. The contradictory results reflect difficulties in using observational studies to predict results of intervention in the individual. Data collected from population‐based registries need to be adjusted continuously to reflect changes in care. What's new?: Despite intensified treatment, with increased frequency of self‐monitored blood glucose measurements and insulin injections/boluses in individual patients, no significant improvement in metabolic outcome at the population level was observed. The benefits of intensifying treatment on the individual level cannot be translated into improved overall metabolic control in this registry‐based epidemiological study. Population‐based registries offer a valuable basis for following the quality of care of the population, but it is difficult to change registration practice fast enough to reflect the rapid evolution of treatment methods in the clinical setting.